The Temple Scroll—The Longest and Most Recently Discovered Dead Sea Scroll - Yadin, Yigaʾel (The Biblical archaeology review, 1984)
On August 1, 1960, I received a letter from a man who identified himself as a Virginia clergyman. The letter stated that the writer was in a position to negotiate the sale of "important, authentic discoveries of Dead Sea Scrolls." Obviously, he contacted me because of my intimate involvement in Israel’s acquisition of the […]